SOSIALISASI KONSEP STRUKTUR BANGUNAN MIXED USE AL-AMIN LIVING LAB DAN INDUSTRIAL PARK DI DESA SAMPE CITA KECAMATAN KUTALIMBARU - Hendra Fahruddin Siregar; Dadang Subarna; Melly Andriana; Purba, M. Ali Tami (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2024)
Mixed-use building refers to the combination of several different functions in one building, such as residential, office, shopping and recreational functions built on one site. Designing a mixed-use building structure requires careful planning and considers various factors such as functional needs, aesthetics and energy conservation. In addition, the design of mixed use buildings has various different functions in one area. Floor & Dag Plates Using Plain Reinforcing Steel with Quality Fy = 240mpa (Ø8mm). From the design results, several types of plate thicknesses are obtained according to the workloads that must be accommodated on it. the following are the moments acting on the floor & dag plates. reinforcement calculations are carried out using the capacity design method (capacity strength design) in accordance with SNI 2847-2019. The concept of capacity design in question is to control the formation of plastic joints at predetermined locations. The SAP2000 program can directly calculate the feasibility of structural dimensions and the required reinforcement area from the results of the input program process. In the SAP2000 program, the concrete regulations used are concrete regulations in the United States ACI-318-05/IBC 2003 which in some ways differ from concrete regulations in Indonesia SNI 2847-20219. It is necessary to make adjustments to the regulations that apply in Indonesia. The internal force from the SAP2000 program is selected from the loading combination that produces the field moment and the fulcrum moment at the maximum column face plane. The bending reinforcement and shear reinforcement of the beam can be read directly from the output of the SAP2000 program in the form of information on the required reinforcement area.